Wide localized solitons in systems with time- and space-modulated nonlinearities - Arroyo Meza, L. E. [UNESP]; De Souza Dutra, A. [UNESP]; Hott, M. B. [UNESP] (American Physical Society (APS), 2012)
In this work we apply point canonical transformations to solve some classes of nonautonomous, nonlinear Schrödinger equations, namely, those which possess specific cubic and quintic (time- and space-dependent) nonlinearities. In this way we generalize some procedures recently published which resort to an ansatz to the wave function and recover a time- and space-independent nonlinear equation which can be solved explicitly. The method applied here allows us to find wide localized (in space) soliton solutions to the nonautonomous, nonlinear Schrödinger equation. We also generalize the external potential which traps the system and the terms of the nonlinearities. © 2012 American Physical Society.